Examining universal access to acute hospital care in Ireland during the first three months of COVID-19: Lessons from the policy process [version 1; peer review: 2 approved] - Sarah Parker; Luisne Mac Conghail; Sara Burke (HRB Open Research, 2024)
Background The onset of the COVID-19 pandemic prompted the Irish state to address unprecedented challenges by prioritising public health and equitable access to care. Confronted with the threat of overwhelmed capacity in acute public hospitals, Ireland, initiated a historic Safety Net Agreement (SNA) with 19 private hospitals in March 2020, marking the inaugural establishment of universal single-tier access to hospital care in Ireland. This research aimed to comprehensively examine the policy process underlying the agreement, deriving insights for the implementation of Universal Healthcare. Methods Employing a retrospective qualitative case study approach, the research examined the policy process, including the content, context, actors, and mechanisms involved in the SNA’s implementation. The study used a dataset of 68 policy documents and conducted seven key informant interviews. Results Responding to the pandemic, Ireland classified COVID-19 as a notifiable infectious disease under the 1947 Health Act, exempting affected patients from public hospital charges. The government swiftly implemented health policy measures for universal access through the SNA, recognising challenges in public healthcare capacity and ethical dilemmas within the two-tier hospital system. The agreement's discontinuation was heavily influenced by private hospital consultants, revealing strained relationships and misunderstandings of the private sector. The ongoing policy drift since the pandemic highlights the need for a reassessment of private-sector strategies to alleviate capacity pressures in Ireland's public health system. The SNA also sparked the consideration of a Universal Health Insurance model for Ireland's hospital care. Conclusions Exploring the policy dynamics at the intersection of public and private healthcare, the study imparts lessons for health system reform. The insights have the potential to contribute to long-term goal alignment, robust governance practices, and trust-building mechanisms for effective public-private collaborations in a two-tier health system, offering valuable guidance for future healthcare policy and implementation.